How to make it as an advertising creative - Veksner, Simon (Lauren King Publishing, 2010)
"Advertising is one of the most exciting industries on the planet. However, getting a job as an advertising creative isn't easy and keeping one can be even harder. This book will teach you the elusive skills that are essential if you are to get a job, survive, thrive and ultimately make it big in this highly competitive industry. It examines the qualities you need to be successful in advertising, beyond being good at actually doing the job. It draws on a wealth of experience, with interviews from seven big-name creatives at top international agencies, offering unique advice. This invaluable book is aimed at anyone who is considering becoming an advertising creative, is studying to become one, or would like to become a better one." -- Provided by publisher.